Nutrition in lifecycle education on the COVID-19 pandemic era - Farah Paramita; Rara Warih Gayatri; Septa Katmawanti; Dian Mawarni; Maurizka Sabrina; Alinda Rahmani; Dhana Alvia Noor; Firda Alya Ramadhiana (University of Merdeka Malang, 2022)
Providing balanced nutrition in the life cycle is important to improve the immune system for disease prevention, especially in the Covid-19 Era. The study showed that balanced nutrition has not been fully applied due to a lack of knowledge. As a promotive and preventive agent for preventing the transmission of Covid-19. Students majoring in public health and alumni of public health play an important role and should be supported with update information based on the recent health situation. This community service aims to increase the knowledge of students and alumni about fulfilling balanced nutrition in every life cycle in the Covid-19 era. This community service activity was carried out in the form of a Nutrition in Lifecycle Series webinar which was held three times with various theme including nutrition for pregnancy, breastfeeding, children and adolescents in the Covid-19 era. Evaluation of this activity was carried out through pre-test and post-test and participants' satisfaction. It showed that there is an increase in the pre-test and post-test scores in this webinar series and all participants are satisfied with this webinar series. It is hoped that this activity can continue with various other interesting themes as a means of upgrading knowledge for students and alumni of the public health department.